Dynamic Monitoring of Hypothyroidism During Pregnancy [Letter] - Pei C; Liu Y; Huang J (International Journal of Women's Health, 2023)
Chenlin Pei, Yuelan Liu, Jingrui Huang Department of Obstetrics, Xiangya Hospital Central South University, Changsha, People’s Republic of ChinaCorrespondence: Jingrui Huang, Department of Obstetrics, Xiangya Hospital Central South University, 87 Xiangya Road, Changsha, 410008, People’s Republic of China, Email jingruihuang@hotmail.com; huangjingrui@csu.edu.cn